2017
DOI: 10.1177/2329488417702476
|View full text |Cite
|
Sign up to set email alerts
|

Communication Preferences of Business-to-Business Buyers for Receiving Initial Sales Messages: A Comparison of Media Channel Selection Theories

Abstract: Recent research on media channel selection theories has called for studies exploring communication in interorganizational business relationships and for specific work functions. The present study addresses this need through an exploration of buyer-seller communication practices in business-to-business contexts. Based on a survey of buyers, it offers a comparison of e-mail and voice mail with an emphasis on preferences for initial or cold call sales messages. The study design compares the explanatory power of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This direct communication is also important nowadays to receive emotional feedback from each other. Anders et al (2020) confirmed in their survey that direct marketing channels are of the utmost importance and mainly use phone calls and F2F meetings to communicate with the salesperson. In times of a pandemic, the author assumes that also online F2F meetings should count for direct channels, where you can see your customer or buyer and conclude on a more personal note.…”
Section: Direct or Single Channelmentioning
confidence: 89%
See 3 more Smart Citations
“…This direct communication is also important nowadays to receive emotional feedback from each other. Anders et al (2020) confirmed in their survey that direct marketing channels are of the utmost importance and mainly use phone calls and F2F meetings to communicate with the salesperson. In times of a pandemic, the author assumes that also online F2F meetings should count for direct channels, where you can see your customer or buyer and conclude on a more personal note.…”
Section: Direct or Single Channelmentioning
confidence: 89%
“…The author found a variety of possible notations for channels in the existing literature. The common terms found in academic literature are marketing channel, media channel, distribution channel as well as sales channel (Polo and Sese, 2016;Anders et al (2020);Käuferl & Reinartz (2015); Lapule & Colla, 2016). In the present article the author uses the term "marketing channel" which are for example: www (Internet), social platforms, phone, face to face (F2F), printed magazines, among others.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, teams rated as well-coordinated (vs. somewhat or poorly coordinated) use synchronous media, such as Web conferencing and the phone, for group projects rather than less synchronous media (Aritz, Walker, & Cardon, 2017). Elsewhere, a study about buyer-seller communication shows that individuals prefer asynchronous email for lean tasks, such as exchanging information, asking questions, and staying in touch, and voice mail/phone for rich tasks like getting to know someone and resolving conflict (Anders, Coleman, & Castleberry, 2017). Last, a study on dyadic conflict has shown that individuals who use synchronous, compared to asynchronous media, cooperate more and feel more related to their partners (Roseth et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%